EARNING CULTURAL VALUES AS A STRATEGIC STEP TO IMPROVE EMPLOYEE PERFORMANCE - Endang Sugiarti; Endah Finatariani; Yasir Terza Rahman (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Employee performance is a reflection of a quality organization. Especially in government institutions, where the main task is public servants. So, having professional employees and integrity is a necessity. This study aims to examine the factors that shape performance, based on organizational values. The qualitative method was chosen as a scientific approach, used to facilitate data collection and analysis. The unit of analysis is an employee of the Religion Ministry of Banten province, with a total sample of 70. The sample technique uses simple random sampling and the research instrument uses a questionnaire. Furthermore, the research data were analyzed using multiple linear regression. The results suggest that the performance of employees in the Ministry of Religion offers more professional work skills. This is intended to make public services more measurable and satisfying to the community.